Calculating the absolute binding free energy of the insulin dimer in an explicit solvent. Issue 2 (3rd January 2020) - Gong, Qiankun; Zhang, Haomiao; Zhang, Haozhe; Chen, Changjun
Abstract : In this paper, we calculate the absolute binding free energy of an insulin dimer by steered MD method. The result of −8.97 kcal mol −1 is close to the experimental value −7.2 kcal mol −1 . We also analyze the residue–residue interactions. Abstract : Insulin is a significant hormone in the regulation of glucose level in the blood. Its monomers bind to each other to form dimers or hexamers through a complex process. To study the binding of the insulin dimer, we first calculate its absolute binding free energy by the steered molecular dynamics method and the confinement method based on a fictitious thermodynamic cycle. After considering some special correction terms, the final calculated binding free energy at 298 K is −8.97 ± 1.41 kcal mol −1, which is close to the experimental value of −7.2 ± 0.8 kcal mol −1 . Furthermore, we discuss the important residue–residue interactions between the insulin monomers, including hydrophobic interactions, π–π interactions and hydrogen bond interactions. The analysis reveals five key residues, Vla B12, Tyr B16, Phe B24, Phe B25, and Tyr B26, for the dimerization of the insulin. We also perform MM-PBSA calculations for the wild-type dimer and some mutants and study the roles of the key residues by the change of the binding energy of the insulin dimer.